Potent achiral agonists of the growth hormone secretagogue (ghrelin) receptor. Part 2: Lead optimisation. - Witherington, J; Abberley, L; Briggs, M; Collis, K; Dean, D; Gaiba, A; King, N; Kraus, H; Shuker, N; Steadman, J; Takle, A; Sanger, G; et al. (2008)
A series of small molecule orally bioavailable ghrelin receptor agonists have been identified through systematic optimisation of a high throughput screening hit.